2016
DOI: 10.4314/ijbcs.v9i5.14
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and antioxidant activities of <i>Combretum molle</i> and <i>Pericopsis laxiflora</i>

Abstract: In Burkina Faso as in several African countries, diabetes is becoming a very serious disease and public concern. Patients use both drugs and plants for treatment. Thus, Combretum molle and Pericopsis laxiflora have been identified as plants used in Burkina Faso for the treatment of that disease. The aim of the study was to assess phytochemical components and antioxidant activities of those plants in order to highlight why diabetes patients refer to them. The phytochemical analysis of water, ash quantification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
2
12
1
Order By: Relevance
“…The antioxidant capacity of the fruits was measured by evaluating the ability to react with free radicals using DPPH stable radical. DPPH has been widely used to evaluate the free radical scavenging effectiveness of various plant materials (Fofie et al, 2013;Zintchem et al, 2013;Agboola, 2014;Koevi, 2015). Most free radicals are constantly generated in the human body as byproducts during the normal process of oxidation and they are implicated in many human diseases including accelerated ageing, cancer, cardiovascular diseases, neurodegenerative disease and inflammation (Bhattacharya, 2015).…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…The antioxidant capacity of the fruits was measured by evaluating the ability to react with free radicals using DPPH stable radical. DPPH has been widely used to evaluate the free radical scavenging effectiveness of various plant materials (Fofie et al, 2013;Zintchem et al, 2013;Agboola, 2014;Koevi, 2015). Most free radicals are constantly generated in the human body as byproducts during the normal process of oxidation and they are implicated in many human diseases including accelerated ageing, cancer, cardiovascular diseases, neurodegenerative disease and inflammation (Bhattacharya, 2015).…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…It is reported that C. molle has Saponins, Triterpenes, glycosides, phenols, flavonoids, phenolic compounds, saponin, and alkaloids and anthraquinones [ 15 ]. Thus, the observed activity could be attributed to its chemical components such as flavonoids, phenolic compounds, saponin, and alkaloids [ 16 ]. Some of the studies conducted so far have supported that antiplasmodial activities of plant extracts could be mainly linked to the range of compounds such asterpenes, steroids, coumarins, flavonoids, phenolic acids, lignans, xanthones, anthraquinones, berberine, limonoids, naphthoquinones, sesquiterpenes, quassinoids, indole and quinoline alkaloids [ 17 ].…”
Section: Main Textmentioning
confidence: 99%
“…[1][2][3][4][5] Scientific research reveals that the therapeutic power of herbal plant is as a result of the vast phytochemical properties inherent in them and not just because of the plants shapes as claimed by traditional users. 6,7 Global herbal products are becoming the hub of research in treatment of diseases because of its little or no side effects. 8 Diarrhoea has been described as a state of one having abnormal frequent bowel movement or passing loose fluid stool.…”
Section: Introductionmentioning
confidence: 99%